Reproductive factors and epithelial ovarian cancer survival in the EPIC cohort study. - Beevi,J; Gunter,MJ; Fortner,RT; Tsilidis,KK; Weiderpass,E; Charlotte,Onland-Moret N; Dossus,L; Tjønneland,A; Hansen,L; Overvad,K; Mesrine,S; Baglietto,L; et al. (British Journal of Cancer, 2015)
BACKGROUND: Reproductive factors influence the risk of developing epithelial ovarian cancer (EOC), but little is known about their association with survival. We tested whether prediagnostic reproductive factors influenced EOC-specific survival among 1025 invasive EOC cases identified in the European Prospective Investigation into Cancer and Nutrition (EPIC) study, which included 521 330 total participants (approximately 370 000 women) aged 25-70 years at recruitment from 1992 to 2000. METHODS: Information on reproductive characteristics was collected at recruitment. Cox proportional hazards regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs), and multivariable models were adjusted for age and year of diagnosis, body mass index, tumour stage, smoking status and stratified by study centre. RESULTS: After a mean follow-up of 3.6 years (±3.2 s.d.) following EOC diagnosis, 511 (49.9%) of the 1025 women died from EOC. We observed a suggestive survival advantage in menopausal hormone therapy (MHT) users (ever vs never use, HR=0.80, 95% CI=0.62-1.03) and a significant survival benefit in long-term MHT users (5 years use vs never use, HR=0.70, 95% CI=0.50-0.99, Ptrend=0.04). We observed similar results for MHT use when restricting to serous cases. Other reproductive factors, including parity, breastfeeding, oral contraceptive use and age at menarche or menopause, were not associated with EOC-specific mortality risk. CONCLUSIONS: Further studies are warranted to investigate the possible improvement in EOC survival in MHT users.British Journal of Cancer advance online publication, 10 November 2015; doi:10.1038/bjc.2015.377 www.bjcancer.com.